2019
DOI: 10.1108/mrjiam-11-2018-0886
|View full text |Cite
|
Sign up to set email alerts
|

Innovation drivers in Ecuadorian manufacturing

Abstract: Purpose The purpose of this paper is to study which are the drivers of different types of innovations for manufacturing firms. The considered innovation types are product, process, organizational and marketing innovations. In addition, this study also aims to understand why most types of innovation (with the exception of organizational innovation) have decreased over time. Design/methodology/approach The two non-overlapping waves of the Ecuadorian National Innovation Activities Survey 2013 and 2015 (NIAS) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…This finding could even point to a potential improvement in the allocation of innovative efforts in developing countries, with a focus on capital investment. The notion that embodied technology in capital goods is significant for developing countries and can contribute to fostering future innovation is well‐supported by studies such as Navarro et al (2010), Dabla‐Norris et al (2012), Goedhuys and Veugelers (2012), and Rochina‐Barrachina & Rodríguez (2019). Furthermore, this idea is also evident in more recent papers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This finding could even point to a potential improvement in the allocation of innovative efforts in developing countries, with a focus on capital investment. The notion that embodied technology in capital goods is significant for developing countries and can contribute to fostering future innovation is well‐supported by studies such as Navarro et al (2010), Dabla‐Norris et al (2012), Goedhuys and Veugelers (2012), and Rochina‐Barrachina & Rodríguez (2019). Furthermore, this idea is also evident in more recent papers.…”
Section: Discussionmentioning
confidence: 93%
“…As countries develop, firms' R&D investments capable of creating new technologies are expected to replace a more supply‐dominated process, which operates through the acquisition of available technology embodied in fixed capital (Goedhuys & Veugelers, 2012). In particular, for the Ecuadorian economy, it has been found that one of the drivers of firms' innovative outputs is investment in capital goods (Rochina‐Barrachina & Rodríguez, 2019). Therefore, if partial crowding‐out is accompanied by increased investment in capital goods by financially constrained firms, it could indicate a more effective allocation of funds towards innovation strategies commonly observed in developing countries, involving the assimilation of new technologies embedded in capital goods.…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a los resultados inferenciales, se encontró dentro el modelo estructural que la competencia interpersonal influye sobre la creación de redes de manera significativa y positiva (β = .668; t = 7.691; p < 0.001; Q 2 = .254). No obstante, la relación entre la competencia individual y la creación de redes no fue significativa estadísticamente hablando, según los resultados obtenidos mediante el programa SmartPLS 3 (Ringle et al, 2015).…”
Section: Resultsunclassified